Mniejszość niemiecka w Ołomuńcu w okresie pierwszej Republiki Czechosłowackiej = The german minority in Olomouc in the period of the first Czechoslovak Republic - Cingelová, Gabriela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the transformations which took place after 1918 in the German-Czechoslovak relations, including - in particular - Olomouc, the so-called language enclave, that is an area inhabited to a large extent by population of German origin.
Keywords: Czechosłowacja; Ołomuniec; mniejszość niemiecka; dwudziestolecie międzywojenne; Czechoslovakia; Olomounc; German minority; The Interwar Period